Analisis Fenomena Penuturan Bahasa Indonesia Oleh Konten Kreator Youtube Asing - Tawarika M. Pandiangan; Alissa P. Simbolon; Poliman Padang; Rian T R Simanjuntak; Ika Febriana (Lembaga Pengembangan Kinerja Dosen, 2024)
Speaking Indonesian is very important for foreign content creators who are used as a magnet to attract Indonesian audiences. Speaking Indonesian is considered to be an understanding of Indonesian nationalism. Seeing this paradigm, quite a few people assume that this country has received appreciation because foreigners are considered to show their love for Indonesia through their willingness to speak Indonesian. We aim to identify competencies that influence viewing satisfaction and channel loyalty. The research method used is a literature study with a phenomenological approach. Search for, collect and understand information that strengthens each researcher's argumentation through secondary data sources. To respond to every video broadcast by a foreign content creator in an intelligent way, the public needs to have a critical and selective attitude. The public must develop the ability to sort the information they receive, distinguishing between content that is educational and informative and that which is simply entertainment without substance. This can be done by increasing media and information literacy, and always cross-checking the information provided.